Prospects for a Geographical Indication (GI): Evaluation of the Willingness to Pay (WTP) of Two Food Products: Peanut Oil (Agonlinmi) and Wafers (Kwlikwli) of the Agonlin Area’s of Benin - VIDEGLA, Euloge; Floquet, Anne; MONGBO, Roch L.; TOSSOU, Hermann; ADJOVI, Gildas (My University, 2016)
The concept of Geographical Indication (GI) is a local development tool. In 2010, on ten thousand GIs identified in the world, Africa had none. However Africa has food products that have reputations or specific characteristics links to their origin. This is the case of two peanut food sub products (Agonlinmi and kwlikwli) in Benin, that undergoing counterfeits. This study aims to assess consumer‟s willingness to pay for these two products. This assessment is carried out on a sample of 400 Agonlin oil consumers and 150 kwlikwli consumers selected randomly in the city of Cotonou and surroundings and also in the Agonlin area. The assessment was made using hedonic price method. Quality attributes and implicit price of both products were calculated. The results showed that the quality attribute variable "geographical origin" of the two products is not significant. Prices of quality attributes "color" for Agonlin oil and "crispness" for Kwlikwli are significant. The potential for GI protection for the two products is not evident on the basis of this analysis of willingness to pay. It will take more research by other analysis or investigative tools.
Keywords: Geographic indications; Willingness to pay; Implicit prices; Attributes; Agonlinmi; Agonlin Kwlikwli.